Information‐seeking lobbying and strategic stockpiling under trade policy uncertainty - Yang, Bo (Strategic Management Journal, 2026)
Abstract Research Summary This study investigates how firms engage in information‐seeking lobbying to address trade policy uncertainty. I argue that lobbying enables firms to gain early insights into forthcoming tariff actions, allowing them to strategically stockpile products likely to be targeted. Using shipping records of US firms during the 2018 US–China trade war, I find that lobbying firms increased imports of soon‐to‐be‐tariffed products before tariff lists were publicly released, compared to non‐lobbying firms. This selective stockpiling pattern disappeared after tariff announcements. Further analysis shows that lobbying firms were less likely to request tariff exemptions for products they had preemptively stockpiled, suggesting that information‐seeking lobbying during policy formulation provides an additional benefit by reducing the need for costly government engagement during the implementation phase. Managerial Summary To manage heightened trade policy uncertainty, firms often adjust global supply chains or engage with the government—but how can they integrate these strategies? This study proposes that firms can engage in lobbying not just to influence policy outcomes, but to gain early insights into pending trade actions. Using data from the 2018 US–China trade war, I find that lobbying firms stockpiled more of the products that were later targeted by tariffs before those tariffs were publicly announced. These firms were also less likely to request tariff exemptions for products they had preemptively stockpiled, indicating potential cost savings by avoiding expensive government engagement. The findings underscore the strategic value of early‐stage lobbying and highlight the importance of coordination between government affairs and operation departments.